Common fixed points of a finite family of multivalued quasi-nonexpansive mappings in uniformly convex banach spaces - Aunyarat Bunyawat (2018)
In this paper, we introduce a one-step iterative scheme for inding a common ixed point of a inite family of multivalued quasi-nonexpansive mappings in a real uniformly convex Banach space. We establish weak and strong convergence theorems of the proposed iterative scheme under some appropriate conditions. © 2013 Iranian Mathematical Society.